2015
DOI: 10.1016/j.eats.2015.07.029
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopically Assisted Treatment of Acute Dislocations of the Acromioclavicular Joint

Abstract: Arthroscopically assisted treatments for dislocations of the acromioclavicular joint combine the advantages of exact and visually controlled coracoid tunnel placement with the possibility of simultaneous treatment of concomitant injuries. The clinical results of previous arthroscopically assisted techniques have been favorable at midterm and long-term follow-up. The presented surgical technique combines the advantages of arthroscopically positioned coracoclavicular stabilization with an additional suture cord … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
37
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 9 publications
1
37
0
Order By: Relevance
“…To our knowledge, a handful of other ST CC ligament reconstruction techniques have been described. 6,16,21,24,32 Some favorable results were published, but the overall outcomes are mixed. Beitzel et al 4 performed a biomechanical study in 2011 in which the ST CC ligament reconstruction technique (1 suture pulley and 2 buttons) and the DT CC ligament reconstruction technique (1 suture pulley and 3 buttons) demonstrated a high load to failure, with superior translation equal to the stability of a native AC joint.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, a handful of other ST CC ligament reconstruction techniques have been described. 6,16,21,24,32 Some favorable results were published, but the overall outcomes are mixed. Beitzel et al 4 performed a biomechanical study in 2011 in which the ST CC ligament reconstruction technique (1 suture pulley and 2 buttons) and the DT CC ligament reconstruction technique (1 suture pulley and 3 buttons) demonstrated a high load to failure, with superior translation equal to the stability of a native AC joint.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, recent biomechanical and clinical studies have advocated for reconstruction or repair of both the CC and AC capsule for stabilization. [4][5][6][7][8][9][10] The acromioclavicular ligament complex (ACLC) has been reported as the primary posterior stabilizer of the AC joint. [11][12][13][14] A previous biomechanical study demonstrated that dissection of the entire ACLC (with intact CC ligaments) reduced the resistance force of the AC joint against posterior translation to less than 25% when compared with the native ligament complex.…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of these publications, multiple surgical techniques have been developed recently to better reconstruct the anatomic structures of the AC capsule in addition to CC ligament reconstruction. 1,3,7,10,14,19,20 Such techniques range from intramedullary reconstruction to cross-shaped cerclage of the superior ligaments to 1-hole drill techniques with biological grafts. However, a detailed analysis of the individual segments of the AC capsule was not available in the literature until now.…”
Section: Discussionmentioning
confidence: 99%
“…8,17 Recent surgical procedures focus on anatomic reconstruction of the AC capsule in combination with the coracoclavicular (CC) ligaments. 1,3,20 Consequently, many of these techniques combine reconstruction of the CC ligaments with reconstruction of the capsular structures. Such procedures should optimally replicate the joint's mechanical function and improve clinical results.…”
mentioning
confidence: 99%